Model Penentu Market Price of Share Pada Sektor Manufaktur Yang Terdaftar di BEI - Tita Deitiana; Renata Chriselda (Jurnal Manajemen dan Bisnis Indonesia, 2017)
The purpose of this study to investigate the factor that influence Market Price of Share in Manufacture companies. The second objective is to identify influence independent variable to dependent variable. Data for this study is the financial ratios calculated from the financial statement of Manufacture in Indonesia Stock Exchange over the five year period 2010 until 2014. The number of sample with purposive sampling method are 8 company as part of 119 Manufacture company. This study also measured by multiple linear regression method with software E-views 7.2. The result show that there is significant relationship between Dividend per Share, Earnings per Share, and Book Value also there is not a significant relationship between Dividend Payout Ratio, Return on Networth, Price Earnings Ratio and Size with Market Price of Share. Keyword: Market Price of Share, Dividend per Share, Earnings per Share, Book Value, Dividend Payout Ratio, Return on Networth, Price Earnings Ratio, and Size